IMPLEMENTASI PROGRAM KELUARGA HARAPAN DI DESA KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Setya Darma, Aldho (JURNAL KEBIJAKAN PUBLIK, 2025)
The Family Hope Program is one of the programs that aims to provide assistance to the underprivileged, to reduce poverty, and improve the quality of existing human resources. This study aims to determine how the implementation of the Family Hope Program is in Kubang Jaya Village, Siak Hulu District, Kampar Regency. The urgency of this research lies in the need to evaluate program implementation to ensure it is targeted and effective. This research is a qualitative research with data collection techniques in this research using several methods, namely literature studies, observations, and interviews. There are several problem factors that are related to the substance of the policy, the behavior of the implementer's duties, resources and participation of the target group. In the theory of policy implementation put forward by Muchlis Hamdi (2014) which consists of resources, participation of the target group, the behavior of the implementer's duties and the substance of the policy. The implementation of PKH is expected to improve the welfare of the community in terms of improving the standard of living of socio-economic, education, and health, especially in poor communities. The purpose of this study is to determine the Implementation of PKH and the Supporting and Inhibiting Factors of PKH Implementation. The implementation of this PKH program has not gone well because there are several indicators that cause the program not to run smoothly.